Communicating the Value of Waste Management to Customers: Focus on Website Content - Repovienė, Rūta; Pažėraitė, Aušra (Organizations and Markets in Emerging Economies, 2023)
Understanding waste management processes and their role in positive environmental changes is significant at various levels. Among members of the public, awareness can be fostered by communicating the benefits of waste management and responding to the needs of individuals.The web is one of the communication channels that is easily accessible to many users and managed by waste management organisations. Therefore, this study aims to explore the combinations of content ideas, forms, and customer value dimensions in communication with society about the value of waste management through a website. Theoretical analysis showed that purposeful communication of customer value can be implemented by utilising different customer value dimensions using content marketing principles.Quantitative content analysis of waste management organisation websites was conducted and directed toward the current state of communication and its patterns. The results revealed that current content focuses on the repetitive communication of functional value through informative articles. Thus, a lack of more diverse content presenting the emotional and social values of waste management was identified.The waste management field can benefit by integrating various customer value dimensions and content marketing theory to identify new opportunities and ways to involve society and achieve the scale of impact needed.The authors would like to thank the European Commission and the REA for the support of the TWIN-PEAKS project. TWIN-PEAKS has received funding from the European Union`s Horizon 2020 research and innovation programme under grant agreement No. 951308.
Keywords: customer value; content marketing; waste management; website content